2022
DOI: 10.20525/ijrbs.v10i8.1505
|View full text |Cite
|
Sign up to set email alerts
|

Budget participation, information asymmetry, and job insecurity as a predictor of budgetary slack

Abstract: Budgetary slack occurs because of the potential difference with the revenue budget target. the difference in potential revenue with the revenue budget target indicates the occurrence of individual behavior lowering the income target to facilitate the achievement of the government budget. The purpose of this study is to empirically prove the effect of budget participation, information asymmetry, and job insecurity that trigger budgetary slack. The population of this research is officials of the Indonesian: Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This often leads to the practice of increasing costs or reducing income from the proper level so that the budget is more easily achieved (Renggadewi, 2020) . Budgetary slack is positively impacted by budget participation activities, according to research by (Tyas et al, 2022). She states that in order to keep employees' optimistic outlook, budgetary slack can be reduced by lowering budget involvement from firm management, eliminating job instability, and increasing oversight to lessen information asymmetry.…”
Section: Russian Journal Of Agricultural and Socio-economic Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…This often leads to the practice of increasing costs or reducing income from the proper level so that the budget is more easily achieved (Renggadewi, 2020) . Budgetary slack is positively impacted by budget participation activities, according to research by (Tyas et al, 2022). She states that in order to keep employees' optimistic outlook, budgetary slack can be reduced by lowering budget involvement from firm management, eliminating job instability, and increasing oversight to lessen information asymmetry.…”
Section: Russian Journal Of Agricultural and Socio-economic Sciencesmentioning
confidence: 99%
“…Previous research examining the relationship between budget participation and budgetary slack showed inconsistent results. Research conducted by Agustina & Suhaidar (2021), Christina & Akbar (2019), Handoyo et al, (2022), Jati & Widhiyani (2020), Precilia & Mimba (2020), Renggadewi (2020), Sulistyawati et al (2023) and Tyas et al (2022) shows that budget participation has a positive influence on the budgetary slack, where the higher the budget participation in preparing the budget, the higher the opportunity or opportunity to make budgetary slack. Different things were shown by research by Ardianti et al (2021) and Okoye & Nwamaka, (2022) which show that budget participation results have a negative influence on the budgetary slack.…”
Section: Introductionmentioning
confidence: 99%
“…The second factor that is considered to trigger the emergence of budgetary slack is information asymmetry (Tyas et al, 2021;Sarwendhi, 2021;Rosmilasari & Hartiyah, 2021). Based on agency theory, conflicts of interest often occur between superiors (principals) and trusted subordinates (agents) because both parties are competing to do something in their respective interests.…”
Section: Preliminarymentioning
confidence: 99%
“…Budget participation is the process of preparing a budget with a bottom-up approach that involves parties, both superiors and subordinates, who influence budget determination and the achievement of the budget itself, or in other words, budget participation opens up opportunities for subordinates to participate in budgeting. the agency where he works is compiled (Tyas et al, 2021). Arista & Syofyan (2019) stated that, the many parties involved when the budget is prepared can influence the determination of budget targets, because the budget is proposed based on the interests of certain parties.…”
Section: Budget Participationmentioning
confidence: 99%
“…Information asymmetry can be exploited by managers to create budgetary slack, as they have more knowledge about the actual resource requirements and operational realities of the organization (Anggraini et al, 2023). In addition, Tyas et al (2022) shows that budget participation, information asymmetry, and job insecurity have a positive effect on budgetary slack. It shows that the high budget participation of public sector employees can trigger budgetary slack and information asymmetry motivates budget implementers to take action to reduce revenue targets and increase government spending the high budget participation of public sector employees can trigger budgetary slack.…”
Section: Theoretical Frameworkmentioning
confidence: 99%